PENGARUH DISIPLIN KERJA, KOMITMEN DAN IKLIM ORGANISASI TERHADAP SEMANGAT KERJA PEGAWAI PENGURUS BARANG MILIK DAERAH PEMERINTAH KABUPATEN DAIRI - Tumanggor, Dwi Oktaria S.; Pardede, Erwin; Sianturi, Marudut (LPPM Universitas Darma Agung, 2020)
There are many factors influencing work morale, including organizational climate, work environment, work discipline, leadership, commitment, compensation, career development, and promotion and so on. However, this research only examines the factors of work discipline, commitment and organizational climate. This study aims at determining the effect of work discipline, commitment and organizational climate partially and simultaneously on the morale of employees of the Regional Property Management of the Dairi Regency Government. The population of this research is 48 employees. In determining the number of samples, saturated samples are used so that the sample is 48 employees. Data collection techniques in this study are questionnaires, interviews and documentation studies. While the data analysis techniques used are the classical assumption test, multiple regression, partial test, simultaneous test and the coefficient of determination. The results show that the work discipline variable has an effect on the morale of employees at the Regional Property Management of the Dairi Regency Government, where the better work discipline, the higher the morale will also be. The commitment variable has a significant effect on the morale of employees at the Regional Property Management of the Dairi Regency Government, where the better the work commitment, the higher the morale will also be. Organizational climate has a significant effect on the morale of employees at the Regional Property Management of the Dairi Regency Government, where the better the organizational climate, the higher the morale will be. Simultaneously, there is a significant influence on the influence of discipline, commitment, and organizational climate on employee morale. It is recommended that the Head of the Regional Property Management of the Dairi Regency Government should provide an example and provide disciplinary sanctions according to violations committed by subordinates, encourage employee involvement in solving every problem, and provide strong encouragement so that employees commit to work.